Assessment of carbon emissions of potential Philippine transport policies using TransCO2 - Gabriel, Ron Michael L.; Mangalindan, Bryan Joseph L.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Due to the increasing threat of climate change and its harmful effects worldwide, reducing Greenhouse Gas Emissions has been one of the top priorities of international institutions. The transport sector, being one of the highest contributors of CO₂ in any country, especially for a developing country like the Philippines, is one of the priorities if any attempt of significant greenhouse gas emissions reduction will be made. The study aims to assess the policies that may be implemented in the country based on local government proposals and the Kuala Lumpur Strategic Transport Plan. The project scenarios tackled by the study are: the deployment of 100,000 units of Electric Tricycles, 25,000 units of Electric Jeepneys and the 2016 Euro 4 Fuel Standard set by the Dept. of Energy in one scenario and the use of the same emerging technologies in an attempt to meet an average fuel economy of 4.4L/100 km in another. TransCO₂, a spreadsheet-based application, was used to evaluate the project scenarios supposed they were implemented. TransCO₂ was able to run simulations, but both project scenarios produced higher emissions. Project scenario 1 showed an improving trend as veh-km of the emerging technologies increased annually. Project scenario 2 showed a worsening trend and this may be attributed to the lack of scrappage data of existing poor fuel efficiency vehicles.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Atmospheric carbon dioxide -- Measurement; Automobiles -- Fuel consumption